Study of the Side effects profile of different antihypertensive drugs among the Hypertensive patient - Shrestha, RK; Khan, GM; Thapa, P; Koju, R (Nepalese Heart Journal, 2013)
Background Hypertension is the leading cause of morbidity and mortality worldwide. Because hypertension is usually asymptomatic yet requires long term therapy, consideration of potential of undesirable effects of drugs used for its treatment is important for making the appropriate choice. In this context, a precise understanding typical adverse reaction profile of the different drugs is essential. Objective This study was done to assess the side effects profile of different antihypertensive drugs (calcium channel blocker, beta blocker, ACE inhibitor) among the hypertensive patient. Methods A mixed retrospective & prospective cross sectional study of 61 patients was done at Medical Out Patient Department of Dhulikhel Hospital KUTH were included in the study. Result Dry cough was experienced by most of the patients (66.7%) and both dry cough and dizziness was reported by only one patient (6.7%) taking enalapril. In case of atenolol, bradycardia, dizziness and insomnia were experienced by same number of patients (14.3%) separately. Among amlodipine users, side effects experienced were peripheral edema (23%), flushing (2.6%), dyspnoea (2.6%), headache (5.1%), dizziness (2.6%), palpitation (2.6%) and insomnia (2.6%).Patients on enalapril had significantly more complaints regarding side effects (73.3%) compared to those taking amlodipine (41%) (OR=4, p=0.033) and atenolol (42.9%).There was no significant difference in the occurrence of side effects between enalapril- atenolol (p >0.05) and amlodipine- atenolol (p >0.05). Conclusion Although all three drugs were well tolerated, more side effects were seen in case of enalapril. Enalapril has 4 times higher rate of side effects than amlodipine. DOI: http://dx.doi.org/10.3126/njh.v9i1.8344 Nepalese Heart Journal Vol.9(1) 2012 pp.25-29